Laminated film and article
By designing a laminated film with a protective film, a coating, a resin substrate and an adhesive layer, the surface characteristics of the coating are controlled, and the problem that changes in the gloss of the adhesive and surface roughness affect the optical characteristics and durability of the laminated film are solved, thereby achieving stable optical characteristics and excellent durability.
Patent Information
- Application Number
- CN202380061383.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-08-23
- Filing Date
- 2023-08-22
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2043-08-22
AI Technical Summary
The prior art is difficult to maintain the optical properties and durability of the laminated film when the gloss and surface roughness of the adhered body are changed.
A laminated film is designed with a protective film, a coating, a resin substrate and an adhesive layer in turn. By controlling the peeling speed and surface characteristics of the protective film and the coating, the surface roughness and free energy of the coating are ensured to meet a specific range, thereby maintaining the optical characteristics and durability of the laminated film.
The laminated film is achieved without being affected by the gloss of the adhesive and surface roughness, providing stable optical properties and maintaining excellent durability under strict moisture resistance conditions.
Smart Images

Figure CN119768273A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to laminated films and articles. Background Art
[0002] Laminated films are used to protect the surface of articles used outdoors or to impart design characteristics (for example, see Patent Documents 1 to 4).
[0003] Prior art literature
[0004] Patent Literature
[0005] Patent document 1: Japanese Patent Application Publication No. 2018-053193.
[0006] Patent document 2: Japanese Patent No. 5426159.
[0007] Patent document 3: International Publication No. 2016 / 010041.
[0008] Patent document 4: International Publication No. 2017 / 047600. Summary of the invention
[0009] Problems to be solved by the invention
[0010] However, an article to which a resin plate or a laminate film is attached (hereinafter referred to as an adherend) changes its surface shape and optical characteristics over time.
[0011] For example, the gloss of the originally high-gloss adherend decreases, the haze increases, and the visual recognition decreases. On the other hand, in order to protect privacy, suppress reflection of sunlight and reduce surrounding dizziness, the gloss of the originally low-gloss adherend increases and the haze decreases, and there is a problem of these gloss properties being reduced.
[0012] Furthermore, when a laminated film is attached to an article that deteriorates over time, it is difficult to impart optical properties from high gloss to low gloss because the film is affected by the surface shape of the article.
[0013] Therefore, an object of the present invention is to provide a laminated film which provides optical properties corresponding to requirements without being affected by the gloss and surface roughness of an adherend and has excellent durability even under conditions where the moisture resistance of the adherend is severe.
[0014] Furthermore, another object of the present invention is to provide an article using such a laminate film.
[0015] Means for solving problems
[0016] In order to solve the above-mentioned problems, the present invention provides the following solutions.
[0017] [1] A laminate film comprising a protective film, a coating, a resin substrate, and an adhesive layer in sequence, wherein the protective film is adjacent to the coating, and when the protective film is peeled off from the laminate film at a speed of 5.0 mm / sec and the laminate film without the protective film is set as a laminate film L, the surface roughness Rac of the surface of the coating of the laminate film L on the side opposite to the resin substrate and the surface roughness Rap of the coating side of the protective film after peeling satisfy Formula 1.
[0018] 50.0≤(Rac / Rap)×100≤210.0 Formula 1
[0019] Furthermore, the surface free energy γac of the surface of the coating layer of the laminate film L on the opposite side to the resin substrate and the surface free energy γap of the coating layer side of the protective film after peeling satisfy Formula 2.
[0020] 50.0≤(γac / γap)×100≤110.0 Formula 2
[0021] The 60° glossiness G(IL) of the laminated film L and the 60° glossiness G(IC) of the laminated film L in the composite of the laminated film L and the adherend when the laminated film L is bonded to the adherend satisfy Formula 3.
[0022] 85.0≤(G(IC) / G(IL))×100≤110.0 Formula 3
[0023] Furthermore, the Martens hardness of the coating layer of the laminate film L satisfies Formula 4.
[0024] 2N / mm 2 ≤HM(L)≤50N / mm 2 Formula 4
[0025] The 60° gloss G(A) of the laminated film L after the wet heat test of the composite under conditions of humidity 85% and temperature 85°C and the 60° gloss G(IC) of the laminated film L before the wet heat test of the composite under conditions of humidity 85% and temperature 85°C satisfy Formula 5.
[0026] 70.0≤(G(A) / G(IC))×100≤120.0 Formula 5
[0027] [2] The laminated film according to [1], wherein the coating layer is formed of at least one layer, and the laminated film is composed of a protective film, a transparent layer, a design layer, a resin substrate, and an adhesive layer laminated in this order.
[0028] [3] A laminated film as described in [1] or [2], wherein the laminated film is formed by a structure including a design layer between a resin substrate and an adhesive layer of the laminated film, and the laminated film is sequentially laminated with a protective film, a coating layer, a resin substrate, a design layer and an adhesive layer.
[0029] [4] The laminate film according to any one of [1] to [3], wherein the Tg of the coating layer of the laminate film L after curing is 25.0°C to 120.0°C.
[0030] [5] The laminated film according to any one of [1] to [4], wherein the stretching ratio of the laminated film L is 50% to 300%.
[0031] [6] The laminated film according to any one of [1] to [5], wherein the coating layer is composed of one or more selected from the group consisting of acrylic resin, polycarbonate polyol, fluororesin, and silicone resin.
[0032] [7] An article, wherein the article includes an adherend and a laminated film L, wherein the laminated film L is obtained by peeling the protective film from the laminated film described in any one of [1] to [6], and the adhesive layer of the laminated film L is in contact with the adherend.
[0033] Effects of the Invention
[0034] According to the present invention, it is possible to provide a laminated film which is not affected by the gloss and surface roughness of an adherend, provides optical properties that meet requirements, and suppresses a decrease in the durability of an article. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 It is a schematic diagram showing an example of the layer structure of the laminated film of the present invention.
[0036] Figure 2 Schematic diagram showing an example of the layer structure of the laminate film L.
[0037] Figure 3 This is a schematic diagram showing an example of the layer structure of a composite.
[0038] Figure 4 It is a schematic diagram showing an example of the layer structure of the laminated film of the present invention.
[0039] Figure 5 It is a schematic diagram showing an example of the layer structure of the laminated film of the present invention. DETAILED DESCRIPTION
[0040] Hereinafter, embodiments of the present invention will be described. These descriptions are intended to illustrate the present invention and do not limit the present invention in any way.
[0041] In the present invention, two or more embodiments can be arbitrarily combined.
[0042] In the present specification, unless otherwise specified, a numerical range is intended to include the upper limit and lower limit of the range. For example, 60 to 99 mass % means 60 mass % or more and 99 mass % or less.
[0043] The drawings are drawn with priority given to understanding the present invention, and the sizes and proportions of the components are sometimes not accurate.
[0044] (Laminated Film)
[0045] The laminated film of the present invention is a laminated film having a protective film, a coating, a resin substrate, and an adhesive layer in sequence, wherein the protective film is adjacent to the coating, and when the protective film is peeled off from the laminated film at a speed of 5.0 mm / sec and the laminated film without the protective film is set as a laminated film L, the surface roughness Rac of the surface of the coating of the laminated film L on the side opposite to the resin substrate and the surface roughness Rap of the coating side of the protective film after peeling satisfy Formula 1.
[0046] 70.0≤(Rac / Rap)×100≤210.0 Formula 1
[0047] Furthermore, the surface free energy γac of the surface of the coating layer of the laminate film L on the opposite side to the resin substrate and the surface free energy γap of the coating layer side of the protective film after peeling satisfy Formula 2.
[0048] 50.0≤(γac / γap)×100≤110.0 Formula 2
[0049] The 60° glossiness G(IL) of the laminated film L and the 60° glossiness G(IC) of the laminated film L in the composite of the laminated film L and the adherend when the laminated film L is bonded to the adherend satisfy Formula 3.
[0050] 85.0≤(G(IC) / G(IL))×100≤110.0 Formula 3
[0051] Furthermore, the Martens hardness of the coating layer of the laminate film L satisfies Formula 4.
[0052] 2N / mm 2 ≤HM(L)≤50N / mm 2 Formula 4
[0053] The 60° gloss G(A) of the laminated film L after the wet heat test of the composite under conditions of humidity 85% and temperature 85°C and the 60° gloss G(IC) of the laminated film L before the wet heat test of the composite under conditions of humidity 85% and temperature 85°C satisfy Formula 5.
[0054] 70.0≤(G(A) / G(IC))×100≤120.0 Formula 5
[0055] The adhesive layer fills the deteriorated part to restore transparency, and the coating that can transfer / maintain the shape of the protective film can be selected to have the required optical properties. Not only can the appearance and gloss (60° glossiness) be adjusted, but also the durability of the adherend such as hardness and moisture and heat resistance can be restored.
[0056] Figure 1 Schematic diagram showing an example of the layer structure of the laminated film of the present invention. Figure 1 In the example of FIG. 1 , the laminated film 1 includes a protective film 10 , a coating layer 20 , a resin base material 30 , and an adhesive layer 40 in this order.
[0057] Figure 2 Schematic diagram showing an example of the layer structure of the laminate film L. Figure 2 In the example of FIG. 1 , the laminate film L2 includes a coating layer 20 , a resin base material 30 , and an adhesive layer 40 in this order.
[0058] Figure 3 is a schematic diagram showing an example of the layer structure of a composite. Figure 3 In the example of FIG. 1 , the composite body 3 includes a coating layer 20 , a resin substrate 30 , an adhesive layer 40 , and an adherend 50 in this order.
[0059] Figure 4 Schematic diagram showing an example of the layer structure of the laminated film of the present invention. Figure 4 In the example of FIG. 4 , the laminate film 4 sequentially includes a protective film 10, a transparent layer 60, a design layer 70, a resin substrate 30, and an adhesive layer 40. The laminate film L and the composite have the same structure as the laminate film 1 except that the coating layer has two or more layers.
[0060] Figure 5 Schematic diagram showing an example of the layer structure of the laminated film of the present invention. Figure 5 In the example of FIG. 5 , the laminate film 5 sequentially includes a protective film 10, a coating layer 20, a resin substrate 30, a design layer 70, and an adhesive layer 40. The laminate film L and the composite have the same structure as the laminate film 1 except for the presence or absence of the design layer.
[0061] (Protective film)
[0062] As the film forming the protective film, there is no particular limitation, for example, biaxially stretched films such as biaxially stretched polyester film, biaxially stretched polypropylene film, soft vinyl chloride film, non-stretched polypropylene film, non-stretched polyester film, polyolefin film, modified polyolefin film, polystyrene resin film, polyurethane film, urethane nylon film, polyamide film, polymethylpentene film, polycarbonate film, acrylic resin film, fluorine film and other previously known films can be cited. Among them, the film formed by polyester and / or polyolefin is preferably, especially from the viewpoint of energy-saving low-temperature processability, in the case of requiring formability (extensibility) to be applied to a planar substrate, biaxially stretched polyester film is more preferred, and in the case of requiring formability (extensibility) to be applied to a three-dimensional shape, non-stretched polyester film is more preferred. The thickness of the above-mentioned protective film is preferably 0.01 to 0.5 mm, more preferably 0.02 to 0.3 mm. If it is outside this range, when it acts as a carrier film or when active energy ray curing is performed, the amount of energy required increases to cure the transparent layer coating film, which is not preferred from the viewpoint of economy.
[0063] As the protective film of the present invention, a protective film having a concavo-convex shape on the surface may also be used. If such a film is used, the concavo-convex shape of the protective film is transferred to the coating, and thus, it is preferred from the viewpoint of being able to obtain a design having a matte feel based on the concavo-convex feel. The concavo-convex shape herein is not particularly limited, as long as it is visually recognizable and can obtain a matte feel in the design.
[0064] The protective film may be coated with a release agent on one or both of the surfaces, for example, the surface on the transparent layer side and the surface on the opposite side to the transparent layer side.
[0065] In the laminated film, it is preferred that the surface roughness Rac of the laminated film after the protective film is peeled off at a rate of 5.0 mm / sec and the surface roughness Rap of the side on which the protective film is peeled off satisfy the following formula (1).
[0066] 50.0≤(Rac / Rap)×100≤210.0 (1)
[0067] By satisfying the above formula (1), the concavo-convex shape of the protective film can be appropriately transferred, and desired optical characteristics can be obtained.
[0068] The coating may be two layers, either layer may be a transparent layer, and the other layer may be a design layer.
[0069] When the laminated film includes a design layer, the laminated film is preferably a structure in which a protective film, a transparent layer, a design layer, a resin substrate and an adhesive layer are laminated in sequence, or a structure in which a protective film, a coating layer, a resin substrate, a design layer and an adhesive layer are laminated in sequence.
[0070] When the design layer of the laminated film is formed between the resin substrate and the adhesive layer, it is preferred from the viewpoint of weather resistance because the transparent layer and the resin substrate are provided on the surface side closer to the design layer. In addition, the design layer is coated on a relatively smooth resin substrate, and the design is visually recognized from the transparent layer side, which is preferred from the viewpoint of the orientation of the design layer.
[0071] (Coating: In the case of a two-layer structure, a transparent layer)
[0072] The laminated film of the present invention comprises a coating layer. The coating layer used in the present invention is preferably formed of a thermosetting coating composition or an active energy ray-curable coating composition, and its specific composition is not particularly limited as long as the physical properties of the laminated film are not impaired.
[0073] The coating layer forms the outermost layer when an article is attached, and therefore requires properties such as weather resistance, water resistance, and impact resistance. Therefore, it is preferably a layer formed of a thermosetting coating composition or an active energy ray-curable coating composition that excels in these properties.
[0074] The heat-curable coating composition and the active energy ray-curable coating composition are not particularly limited, and conventionally known compositions can be used. They may be aqueous compositions, solvent-based compositions, and may be one-component or two-component compositions.
[0075] As the above-mentioned thermosetting coating composition, for example, a two-liquid coating composition consisting of a main agent and a curing agent can be cited, wherein the main agent comprises a polyol and a curing catalyst, and the curing agent comprises an isocyanurate compound. By mixing the main agent and the curing agent, the polyol reacts with the isocyanurate compound to obtain a cured coating film. The main agent and / or the curing agent can be heated and / or vacuum degassed before mixing, respectively. Thus, the amount of water contained in the two-liquid coating composition obtained by mixing the two decreases, and the appearance of the obtained coating film is easily improved.
[0076] (Main agent)
[0077] Examples of the resin component of the main agent include, but are not limited to, acrylic resins, alkyd resins, epoxy resins, urethane resins, fluororesins, polyether diols, polyester diols, polycarbonate diols, caprolactone diols, polyether polyols, polyester polyols, polycarbonate polyols, caprolactone polyols, and the like.
[0078] The resin component as the main agent is preferably an acrylic resin. In addition, the coating material preferably uses a mixture of a resin component and an isocyanate compound. If it is such a mixture, it will not show adhesion near room temperature, but by heating the coating, the plasticity of the resin component becomes larger, the resin component is easily deformed, and it shows a certain degree of adhesion.
[0079] Hereinafter, each component will be described in detail.
[0080] (Acrylic resin)
[0081] The weight average molecular weight of the acrylic resin is, for example, 1,000 to 200,000, or preferably 3,000 to 100,000.
[0082] The glass transition temperature (Tg) of the acrylic resin of the coating material is, for example, 0 to 100° C., preferably 10 to 50° C. In one embodiment, the Tg of the acrylic resin of the coating material is 20° C. or higher, 30° C. or higher, 40° C. or higher, 50° C. or higher, 60° C. or higher, or 70° C. or higher. In another embodiment, the Tg of the acrylic resin of the coating material is 80° C. or lower, 70° C. or lower, 60° C. or lower, 50° C. or lower, 40° C. or lower, or 30° C. or lower.
[0083] The proportion of the acrylic resin in the coating material for coating is, for example, 50% by mass or more, preferably 60 to 99% by mass. In one embodiment, the proportion of the acrylic resin in the coating material for coating is 50% by mass or more, 60% by mass or more, 70% by mass or more, 80% by mass or more, or 90% by mass or more. In another embodiment, the proportion of the acrylic resin in the coating material for coating is 99% by mass or less, 90% by mass or less, 80% by mass or less, 70% by mass or less, or 65% by mass or less.
[0084] (Polyol)
[0085] Polyols are film-forming resins. Polyols react with curing agents, for example, by heating to form a cured film. Each polyol molecule has two or more hydroxyl groups. As a result, the hardness of the obtained film tends to increase. Polyols can be used alone or in combination of two or more.
[0086] Preferably, the main agent comprises a polyol (A1) having three or more hydroxyl groups per molecule and a polyol (A2) having two hydroxyl groups per molecule. The ratio of the polyol (A1) to the polyol (A2) is not particularly limited. The ratio of the polyol (A2) may be less than 50% by mass of the total of the polyol (A1) and the polyol (A2), may be less than 40% by mass, or may be less than 30% by mass.
[0087] The hydroxyl value of the polyol is 300 mgKOH / g or more and 1000 mgKOH / g or less. When the hydroxyl value of the polyol is within the above range, the reaction rate of the polyol and the isocyanate compound becomes larger when the main agent and the curing agent are mixed. Therefore, the coating product can be rapidly demoulded from the mold, and productivity is improved. In addition, during the reaction, a certain degree of reaction heat is generated, so it is particularly easy to improve the adhesion of the coating film to the resin substrate.
[0088] When the main agent contains two or more polyols, the apparent hydroxyl value calculated based on the hydroxyl value and mass ratio of each polyol is 300 mgKOH / g or more and 1000 mgKOH / g or less. That is, the main agent may contain a polyol having a hydroxyl value of less than 300 mgKOH / g and / or a polyol having a hydroxyl value of greater than 1000 mgKOH / g.
[0089] The hydroxyl value of the polyol (including the apparent hydroxyl value, the same below) is more preferably 350 mgKOH / g or more, and further preferably 500 mgKOH / g or more. The hydroxyl value of the polyol is more preferably 800 mgKOH / g or less, and further preferably 700 mgKOH / g or less.
[0090] The type of polyol is not particularly limited. As the polyol, for example, polyester polyol, polyether polyol, polycarbonate polyol, polyacrylate polyol and polyol can be cited. They can be used alone or in combination of two or more. Among them, it is preferred that the polyol comprises at least one selected from the group consisting of polyester polyol, polyether polyol and polycarbonate polyol.
[0091] The polyester polyol preferably has a branched structure. The polyester polyol having a branched structure can be prepared, for example, by reacting a trivalent or higher polyol compound with a divalent or higher polycarboxylic acid, and repeating the above reaction as necessary.
[0092] Examples of commercially available polyester polyols include Desmophen VPLS2249 / 1 (manufactured by Sumika Covestro Urethane Co., Ltd.), Desmophen 800 (manufactured by Sumika Covestro Urethane Co., Ltd.), Desmophen XP2488 (manufactured by Sumika Covestro Urethane Co., Ltd.), Kuraray Polyol P-510 (manufactured by Kuraray Co., Ltd.), and Kuraray Polyol F-510 (manufactured by Kuraray Co., Ltd.).
[0093] Polyether polyols include polyethylene glycol, polypropylene glycol, polytetramethylene glycol and their blocks. Polyether polyols can also be prepared by adding ethylene oxide and / or propylene oxide to polyol compounds. Through the above steps, polyether polyols having a divalent, trivalent or higher OH functional group number per molecule can be prepared.
[0094] Examples of commercially available products of polyether polyols include the Sannix series manufactured by Sanyo Chemical Industries, Ltd. Specifically, Sannix GP-250, Sannix GP-400, Sannix PP-200, and Sannix GP-600 may be mentioned.
[0095] The polycarbonate polyol can be produced, for example, by reacting a polyvalent polyol with dimethyl carbonate.
[0096] Examples of commercially available products of polycarbonate polyol include Duranol T5650E (manufactured by Asahi Kasei Corporation), C-590 (manufactured by Kuraray Co., Ltd.), and ETERNACOLL PH-50 (manufactured by Ube Industries, Ltd.).
[0097] Examples of the polyol include ethylene glycol, glycerin, trimethylolpropane, propylene glycol, tetramethylene glycol, and pentaerythritol.
[0098] The weight average molecular weight (Mw) of the polyol is not particularly limited and the Mw of the polyol may be appropriately set according to the hydroxyl value and the like.
[0099] The main agent may contain a polyol having an average hydroxyl number of less than 3. The main agent may contain other film-forming resins other than the polyol. As the film-forming resin, for example, acrylic resins, polyester resins, alkyd resins, polyether resins, polyolefin resins, polyurethane resins, polycarbonate resins, melamine resins, epoxy resins, and carbodiimide resins may be cited. Other film-forming resins may be used alone or in combination of two or more.
[0100] (Curing Catalyst)
[0101] The curing catalyst promotes the curing reaction. The curing catalyst is not particularly limited. From the viewpoint of the promoting effect, as the curing catalyst, for example, at least one of the organometallic catalysts containing a metal element selected from the group consisting of Bi, Zn, Al, Zr and Sn is preferred. Among them, at least one of the organometallic catalysts containing a metal element selected from the group consisting of Bi, Zn, Al and Zr is preferred.
[0102] As an organic metal catalyst containing Bi, for example, bismuth carboxylic acid and its salts can be mentioned. As an organic metal catalyst containing Zn, for example, zinc complex catalysts can be mentioned. As an organic metal catalyst containing Al, for example, aluminum complex catalysts can be mentioned. As an organic metal catalyst containing Zr, for example, zirconium chelate catalysts can be mentioned. As an organic metal catalyst containing Sn, for example, dibutyltin dilaurate, dioctyltin dilaurate, dibutyltin diacetate and other dialkyltin dicarboxylates; tin oxide compounds such as dibutyltin oxide; tin carboxylates such as 2-ethylhexanoic acid tin.
[0103] As commercially available products of organic metal catalysts containing Bi, for example, K-KAT 348 (manufactured by Kusumoto Chemicals, Ltd.) and K-KAT XK-640 (manufactured by Kusumoto Chemicals, Ltd.) can be cited. As commercially available products of organic metal catalysts containing Zr, for example, K-KAT 4205, K-KAT XC-9213, K-KAT XC-A209, and K-KAT 6212 (all manufactured by Kusumoto Chemicals, Ltd.) can be cited. As commercially available products of organic metal catalysts containing Al, for example, K-KAT 5218 (manufactured by Kusumoto Chemicals, Ltd.) can be cited. As commercially available products of organic metal catalysts containing Zn, for example, K-KAT XK-314, K-KATXK-635, K-KAT XK-639, and K-KAT XK-620 (all manufactured by Kusumoto Chemicals, Ltd.) can be cited. Examples of commercially available Sn-containing organometallic catalysts include TVS TIN LAU (manufactured by Nitto Kasei Co., Ltd.).
[0104] For example, relative to 100 mass parts of film-forming resin, the content of curing catalyst is more than 0.25 mass parts and less than 10 mass parts.Thus, the curing reaction of film-forming resin is carried out rapidly.Therefore, by forming the layer formed by coating, the film with excellent outward appearance and physical property can be obtained.Relative to 100 mass parts of film-forming resin, the content of curing catalyst is more preferably more than 0.5 mass parts.Relative to 100 mass parts of film-forming resin, the content of curing catalyst is more preferably less than 7 mass parts.
[0105] (Curing agent)
[0106] The coating film-forming resin such as acrylic resin and polyol is cross-linked by a curing agent to improve the corrosion resistance and durability of the obtained coating film.
[0107] The curing agent contains an isocyanurate compound. The isocyanurate compound is a trimer of an isocyanate compound and has a ring structure.
[0108] The isocyanate compound is not particularly limited, and a known one can be used as a curing agent for a two-component reactive composition. As the isocyanate compound, for example, aromatic diisocyanates such as toluene diisocyanate (TDI), 4,4'-diphenylmethane diisocyanate (MDI), xylylene diisocyanate (XDI), and meta-xylene diisocyanate (MXDI); aliphatic diisocyanates such as hexamethylene diisocyanate (HDI), tetramethylene diisocyanate, 2-methyl-pentane-1,5-diisocyanate, 3-methyl-pentane-1,5-diisocyanate, lysine diisocyanate, and trioxyethylene diisocyanate; alicyclic diisocyanates such as isophorone diisocyanate (IPDI), cyclohexyl diisocyanate, 4,4'-dicyclohexylmethane diisocyanate, norbornane diisocyanate, hydrogenated toluene diisocyanate, hydrogenated xylene diisocyanate, and hydrogenated tetramethylxylene diisocyanate can be mentioned. These can be used alone or in combination of two or more.
[0109] Among them, from the viewpoint of low viscosity, aliphatic diisocyanates are preferred, and HDI is more preferred. The trimers of these isocyanates have particularly high reactivity with polyols. Therefore, they are more suitable for coating formation methods using coating.
[0110] The ratio of the isocyanate group equivalent of the isocyanate compound to the hydroxyl group equivalent of the polyol: NCO equivalent / OH equivalent is preferably 0.5 / 1 to 2 / 1, more preferably 0.9 / 1 to 1.2 / 1. If the equivalent ratio is within the above range, the curability is high and it is particularly suitable for forming a coating by coating.
[0111] The curing agent may include other curing agents except the isocyanurate compound. As other curing agents, for example, amino resin, monomer or dimer of the above-mentioned isocyanate compound, biuret body of the above-mentioned isocyanate compound, block compound of the above-mentioned isocyanate compound, epoxy compound, aziridine compound, carbodiimide compound, oxazoline compound can be cited. They can be used alone or in combination of two or more.
[0112] The content of the curing agent is, for example, 35% by mass or more and 90% by mass or less of the resin solid content of the coating composition. The above-mentioned content of the curing agent is preferably 45% by mass or more, more preferably 55% by mass or more. The above-mentioned content of the curing agent is preferably 85% by mass or less, more preferably 70% by mass or less.
[0113] (Solvent)
[0114] The content of the solvent is 30% by mass or less. According to this embodiment, even in a composition with a small amount of solvent and high viscosity, the aggregation of the glittering particles is suppressed. Therefore, a coating film with a glittering feeling can be formed by coating. The content of the solvent is preferably 20% by mass or less, more preferably 10% by mass or less, and may also be 0%.
[0115] The solvent is not particularly limited and is usually an organic solvent. Examples of the organic solvent include ester solvents such as ethyl acetate, butyl acetate, isopropyl acetate, ethylene glycol monoethyl ether acetate, propylene glycol monomethyl ether acetate, and propylene glycol monoethyl ether acetate; ether solvents such as propylene glycol monomethyl ether, ethylene glycol monomethyl ether, methyl methoxybutanol, ethoxypropanol, ethylene glycol isopropyl ether, ethylene glycol tert-butyl ether, ethylene glycol monoethyl ether, ethylene glycol monobutyl ether, methoxybutanol, and propylene glycol monobutyl ether; alcohol solvents such as methanol, ethanol, butanol, and propanol; ketone solvents such as acetone, methyl ethyl ketone, and methyl isobutyl ketone; aliphatic hydrocarbon solvents such as SWAZOLE, Shellsol, and mineral spirits; and aromatic solvents such as xylene, toluene, Solvesso-100 (S-100), and Solvesso-150 (S-150). These may be used alone or in combination of two or more.
[0116] (other)
[0117] The two-liquid coating composition may also contain other components as required. As other components, for example, additives that can be commonly used in the coating field and the coating field can be cited. Specifically, light stabilizers, ultraviolet absorbers, various pigments, surface regulators, viscosity regulators, antioxidants, ultraviolet preventers, defoamers, catalyst additives, rust inhibitors, anti-settling agents, dispersants, etc. can be cited. These additives can be added to the main agent or to the curing agent. The amount of the additive is not particularly limited and can be appropriately set as required.
[0118] The active energy ray-curable coating composition is a monomer, oligomer or polymer that can be cross-linked and cured by radiation. As the active energy ray-curable resin in the present invention, from the viewpoint of being able to increase the cross-linking density after curing, being able to increase the effect of improving the surface hardness and being able to increase the effect of improving the transparency, it can contain multifunctional (meth)acrylate compounds such as multifunctional (meth)acrylate monomers, multifunctional (meth)acrylate oligomers or multifunctional (meth)acrylate polymers. It should be noted that, here, "(meth)acrylate" means acrylate and / or methacrylate. It should be noted that in this specification, the multifunctional (meth)acrylate compound refers to a compound that does not have a urethane structure, which is a compound that does not contain the following urethane acrylate. For the active energy ray-curable resin, in addition to the above-mentioned multifunctional (meth)acrylate compound, a monofunctional (meth)acrylate compound may also be included.
[0119] The active energy ray-curable resin that can be included in the active energy ray-curable coating composition may include, for example, urethane acrylate. In one embodiment, the active energy ray-curable coating composition includes a polyfunctional (meth)acrylate compound and urethane acrylate.
[0120] As the urethane acrylate, a urethane acrylate monomer, an oligomer, a polymer or a combination of at least two of them can be used. As an example, urethane acrylate, urethane methacrylate, aliphatic urethane acrylate, aliphatic urethane methacrylate, aromatic urethane acrylate, aromatic urethane methacrylate, etc. can be cited. Among them, a multifunctional urethane acrylate oligomer having a molecular weight of about 1,000 to 10,000 can be preferably used.
[0121] The active energy ray-curable coating composition of the present invention may, for example, contain a multifunctional urethane acrylate having 2 or more acrylate groups and an ester skeleton. By containing the multifunctional urethane acrylate, the obtained coating can exhibit sufficient adhesion to the transparent polymer substrate. In addition, by forming a hard coating with a refractive index within the above-specified range, interference streaks can be prevented. The number of acrylate groups is 2 or more, preferably 2 to 4. If it is a monofunctional urethane acrylate, the reactivity decreases, and the adhesion and hardness may decrease depending on the molecular weight. If the number of functional groups is too large, there is a concern that the adhesion is reduced due to curing shrinkage.
[0122] The polyfunctional (meth)acrylate (compound) is obtained, for example, by reacting a polycarbonate diol (a) (hereinafter, sometimes referred to as component (a)), a (meth)acrylate compound (b) containing two hydroxyl groups and two ethylenically unsaturated groups in the molecule (hereinafter, sometimes referred to as component (b)), and a polyisocyanate (c) (hereinafter, sometimes referred to as component (c)).
[0123] As for the above-mentioned polycarbonate diol (a), there can be mentioned a diol having a straight chain or branched chain with 2 to 10 carbon atoms represented by HO-(ROC(=O)-O)-R'OH (wherein, R and R' are the same or different straight chain or branched alkylene groups with 2 to 10 carbon atoms, and the number of carbon atoms is the total number of R and R'). As for R or R' in the above-mentioned formula, specifically, there can be mentioned ethylene, propylene, butylene, pentylene, hexylene, heptylene, octylene, cyclohexylene, neopentylene, nonylene, 2-methyl-1,8-octylene, etc., and two or more of them can also be used in combination. Among them, polycarbonate diol synthesized from 1,5-pentanediol and / or 1,6-hexanediol is preferred. In addition, as component (a), one compound can be used alone, or two or more compounds can be used in combination. These multifunctional acrylates can be used alone, or two or more compounds can be used in combination.
[0124] Specific examples of the (meth)acrylate compound (b) containing two hydroxyl groups and two ethylenically unsaturated groups in the molecule include (meth)acrylic acid adducts of propylene glycol diglycidyl ether, (meth)acrylic acid adducts of 1,6-hexanediol diglycidyl ether, (meth)acrylic acid adducts of ethylene glycol diglycidyl ether, (meth)acrylic acid adducts of 1,4-butanediol diglycidyl ether, (meth)acrylic acid adducts of 1,5-pentanediol diglycidyl ether, (meth)acrylic acid adducts of 1,7-heptanediol diglycidyl ether, (meth)acrylic acid adducts of 1,8-octanediol diglycidyl ether, etc. In addition to these, (meth)acrylic acid adducts of neopentyl glycol diglycidyl ether, (meth)acrylic acid adducts of bisphenol A diglycidyl ether, and (meth)acrylic acid adducts of hydrogenated bisphenol A diglycidyl ether may be mentioned. Among them, acrylic acid adducts of propylene glycol diglycidyl ether and acrylic acid adducts of 1,6-hexanediol diglycidyl ether are preferred.
[0125] The polyisocyanate (c) is not particularly limited, and diisocyanate compounds such as aliphatic diisocyanate compounds, alicyclic diisocyanate compounds, and aromatic diisocyanate compounds can be preferably used. Specifically, toluene diisocyanate, 4,4'-diphenylmethane diisocyanate, xylylene diisocyanate, xylene diisocyanate, hexamethylene diisocyanate, lysine diisocyanate, 4,4'-methylenebis(cyclohexyl isocyanate), methylcyclohexane-2,4 (or 2,6)-diisocyanate, 1,3-(isocyanate methyl)cyclohexane, isophorone diisocyanate, trimethylhexamethylene diisocyanate, dimer acid diisocyanate, dimethoxyaniline can be mentioned. diisocyanate, phenyl diisocyanate, halogenated phenyl diisocyanate, methylene diisocyanate, ethylene diisocyanate, butylene diisocyanate, propylene diisocyanate, octadecylene diisocyanate, 1,5-naphthalene diisocyanate, polymethylene polyphenylene diisocyanate, triphenylmethane triisocyanate, naphthalene diisocyanate, toluene diisocyanate polymer, diphenylmethane diisocyanate polymer, hexamethylene diisocyanate polymer, 3-phenyl-2-ethylene diisocyanate , cumene-2,4-diisocyanate, 4-methoxy-1,3-phenylene diisocyanate, 4-ethoxy-1,3-phenylene diisocyanate, 2,4'-diisocyanate diphenyl ether, 5,6-dimethyl-1,3-phenylene diisocyanate, 4,4'-diisocyanate diphenyl ether, benzidine diisocyanate, 9,10-anthracene diisocyanate, 4,4'-diisocyanate benzyl ester, 3,3'-dimethyl-4,4'-diisocyanate diphenylmethane, 2,6-dimethyl 4,4'-diisocyanatodiphenyl ester, 3,3'-dimethoxy-4,4'-diisocyanatodiphenyl ester, 1,4-anthracene diisocyanate, phenylene diisocyanate, 2,4,6-toluene triisocyanate, 2,4,4'-triisocyanate diphenyl ether, 1,4-tetramethylene diisocyanate, 1,6-hexamethylene diisocyanate, 1,10-decamethylene diisocyanate, 1,3-cyclohexylene diisocyanate, 4,4'-methylene-bis(cyclohexyl isocyanate), and the like.
[0126] As a production example of polyfunctional urethane acrylate, it can be produced by placing the above components (a) to (c) in an organic solvent (e.g., methyl ethyl ketone) and reacting them at elevated temperatures as required. The completion of the reaction is confirmed by the failure to confirm the presence of isocyanate groups by infrared absorption spectroscopy.
[0127] The polyfunctional urethane acrylate preferably has a weight average molecular weight of 20000 to 60000, and more preferably has a weight average molecular weight of 30000 to 50000. If the weight average molecular weight of the polyfunctional urethane acrylate is too high, the viscosity becomes high, the smoothness is impaired, and the interference streaks are deteriorated. If the molecular weight is too low, the viscosity decreases, the smoothness of the coating surface cannot be maintained, and the interference streaks are deteriorated.
[0128] In addition, from the viewpoint of adhesion, the polyfunctional urethane acrylate is preferably a substance having a hydroxyl value of 0 to 20 mgKOH / g, and more preferably a substance having a hydroxyl value of 0 to 5 mgKOH / g. By controlling the hydroxyl value to be low, the effect of maintaining good adhesion after the wet heat test can be obtained. It should be noted that commercially available polyfunctional urethane acrylate can also be used.
[0129] In the present invention, the active energy ray curing resin contained in the active energy ray curing coating composition preferably includes a multifunctional (meth) acrylate compound and a multifunctional urethane acrylate. In this case, the multifunctional urethane acrylate preferably includes 30 to 90 parts by mass, and more preferably includes 50 to 85 parts by mass, relative to 100 parts by mass of the resin component contained in the active energy ray curing coating composition. When the amount of the multifunctional urethane acrylate is less than 30 parts by mass, the adhesion is reduced, and when the amount of the multifunctional urethane acrylate is greater than 90 parts, the hardness of the coating may be impaired.
[0130] There is no particular limitation on the synthesis method of the polyfunctional urethane (meth) acrylate, and for example, it can be obtained by a urethanization reaction of a polyisocyanate compound and a hydroxyl-containing (meth) acrylate. The above reaction is preferred from the viewpoint of being suitable for obtaining a polyfunctional urethane (meth) acrylate having three or more acryloyl groups in one molecule.
[0131] Furthermore, for the purpose of adjusting the molecular weight and molecular flexibility of the multifunctional urethane (meth) acrylate, a known general-purpose polyol is reacted with the polyisocyanate before reacting the polyisocyanate with the hydroxyl-containing (meth) acrylate to produce a chain-extended urethane prepolymer having a terminal isocyanate group, and the product obtained by reacting the chain-extended urethane prepolymer with the hydroxyl-containing (meth) acrylate can also be used as component (A). The polyol is not particularly limited, and examples thereof include ethylene glycol, diethylene glycol, polyethylene glycol, propylene glycol, dipropylene glycol, polypropylene glycol, neopentyl glycol, 1,4-butanediol, 1,6-hexanediol, 3-methyl-1,5-pentanediol, ethylene oxide / propylene oxide adducts, polyester polyols, and ethylene oxide / propylene oxide copolymers.
[0132] The active energy ray-curable coating composition can include, for example, hydroxyl-containing (meth)acrylates. As hydroxyl-containing (meth)acrylates, for example, 2-hydroxyethyl acrylate or methacrylate, 2-hydroxypropyl acrylate or methacrylate, ethylene glycol mono(meth)acrylate, propylene glycol mono(meth)acrylate, 2-hydroxy-3-methoxypropyl acrylate or methacrylate, pentaerythritol triacrylate or methacrylate, N-hydroxymethyl acrylamide or methacrylamide, N-hydroxy acrylamide or methacrylamide, etc. can be cited. These lactone adducts [for example, PCL-FA or PCL-FM series manufactured by Daicel Corporation of Japan, etc.] can also be used.
[0133] Examples of commercially available hydroxyl-containing (meth)acrylates include DPHA (manufactured by Daicel-Cytec Co., Ltd.), PETRA (manufactured by Daicel-Cytec Co., Ltd.: pentaerythritol triacrylate), PETIA (manufactured by Daicel-Cytec Co., Ltd.), Aronix M-403 (manufactured by Toagosei Co., Ltd.: dipentaerythritol pentaacrylate and dipentaerythritol hexaacrylate), Aronix M-402 (manufactured by Toagosei Co., Ltd.: dipentaerythritol pentaacrylate and dipentaerythritol hexaacrylate), Aronix M-400 (manufactured by Toagosei Co., Ltd.: dipentaerythritol pentaacrylate and dipentaerythritol hexaacrylate), SR-399 (manufactured by Sartomer Corporation: dipentaerythritol hydroxypentaacrylate), KAYARAD DPHA (manufactured by Nippon Kayaku Co., Ltd.), KAYARAD DPHA-2C (manufactured by Nippon Kayaku Co., Ltd.), etc. The above products are compounds containing a part of hydroxyl groups in the products.
[0134] In addition, as commercially available products of multifunctional urethane (meth)acrylates having three or more (meth)acryloyl groups in one molecule, specific product names can be cited, for example, bifunctional urethane (meth)acrylates ("UX-2201" or "UX-8101" manufactured by Nippon Kayaku Co., Ltd., "UF-8001", "UF-8003", "UX-6101", "UX-8101" manufactured by Kyoeisha Chemical Co., Ltd., "Ebecryl 244", "Ebecryl 284", "Ebecryl 2002", "Ebecryl 4835", "Ebecryl 4883", "Ebecryl 8807", "Ebecryl 6700" manufactured by Daicel-Cytec Co., Ltd.), trifunctional urethane (meth)acrylates ("UX-2201" or "UX-8101" manufactured by Nippon Kayaku Co., Ltd., "UF-8001", "UF-8003", "UX-6101", "UX-8101" manufactured by Kyoeisha Chemical Co., Ltd., "Ebecryl 244", "Ebecryl 284", "Ebecryl 2002", "Ebecryl 4835", "Ebecryl 4883", "Ebecryl 8807", "Ebecryl 6700" manufactured by Daicel-Cytec Co., Ltd.), Co., Ltd.), "Ebecryl254", "Ebecryl264", "Ebecryl265" manufactured by Daicel-Cytec Co., Ltd.), tetrafunctional urethane (meth) acrylate ("Ebecryl8210" manufactured by Daicel-Cytec Co., Ltd.), hexafunctional urethane (meth) acrylate ("Ebecryl1290k", "Ebecryl5129", "Ebecryl220", "KRM8200", "Ebecryl1290N" manufactured by Daicel-Cytec Co., Ltd.), nine-functional urethane (meth) acrylate ("Ebecryl1290k", "Ebecryl5129", "Ebecryl220", "KRM8200", "Ebecryl1290N" manufactured by Daicel-Cytec Co., Ltd.), Co., Ltd.), 10-functional urethane (meth) acrylate ("KRM7804" manufactured by Daicel-Cytec Co., Ltd.), 10-functional urethane (meth) acrylate ("KRM8452" and "KRM8509" manufactured by Daicel-Cytec Co., Ltd.), 15-functional urethane (meth) acrylate ("KRM8655" manufactured by Daicel-Cytec Co., Ltd.), etc.
[0135] For example, it is a multifunctional (meth)acrylate compound containing at least two (meth)acryloyl groups in the molecule, for example, Aronix M-400, M-450, M-305, M-309, M-310, M-315, M-320, TO-1200, TO-1231, TO-595, TO-756 (all manufactured by Toagosei Co., Ltd.), KAYARD D-310, D-330, DPHA, DPHA-2C (all manufactured by Nippon Kayaku Co., Ltd.), NIKALAC MX-302 (manufactured by Sanwa Chemical Co., Ltd.) and the like commercially available products can be used.
[0136] By using a radiation-curable resin containing the above-mentioned polyfunctional (meth)acrylate compound, polyfunctional urethane acrylate, etc., there is an advantage that a molded decorative laminate film having excellent light resistance and no light degradation due to long-term use can be obtained.
[0137] (Photopolymerization Initiator)
[0138] The active energy ray-curable coating composition of the present invention preferably contains a photopolymerization initiator. Due to the presence of the photopolymerization initiator, the resin component is well polymerized by irradiation with active energy rays such as ultraviolet rays. Examples of the photopolymerization initiator include alkylphenone-based photopolymerization initiators, acylphosphine oxide-based photopolymerization initiators, titanocene-based photopolymerization initiators, and oxime ester-based polymerization initiators. Examples of the alkylphenone-based photopolymerization initiator include 2,2-dimethoxy-1,2-diphenylethane-1-one, 1-hydroxy-cyclohexyl-phenyl-ketone, 2-hydroxy-2-methyl-1-phenyl-propane-1-one, 1-[4-(2-hydroxyethoxy)-phenyl]-2-hydroxy-2-methyl-1-propane-1-one, 2-hydroxy-1-{4-[4-(2-hydroxy-2-methyl-propionyl)-benzyl]phenyl}-2-methyl-propane-1-one, 2-methyl-1-(4-methylthiophenyl)-2-morpholinopropane-1-one, 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)-butanone-1, and 2-(dimethylamino)-2-[(4-methylphenyl)methyl]-1-[4-(4-morpholino)phenyl]-1-butanone. As the acylphosphine oxide-based photopolymerization initiator, for example, 2,4,6-trimethylbenzoyl-diphenyl-phosphine oxide, bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide, etc. As the titanocene-based photopolymerization initiator, for example, bis(η5-2,4-cyclopentadien-1-yl)-bis(2,6-difluoro-3-(1H-pyrrol-1-yl)-phenyl)titanium, etc. can be mentioned. Examples of the oxime ester polymerization initiator include 1,2-octanedione, 1-[4-(phenylthio)-, 2-(O-benzoyl oxime)], ethyl ketone, 1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazole-3-yl]-, 1-(O-acetoxime), oxyphenylacetic acid, 2-[2-oxo-2-phenylacetoxyethoxy]ethyl ester, 2-(2-hydroxyethoxy)ethyl ester, etc. These photopolymerization initiators may be used alone or in combination of two or more.
[0139] Among the above-mentioned photopolymerization initiators, 2-hydroxy-2-methyl-1-phenyl-propane-1-one, 1-hydroxy-cyclohexyl-phenyl-ketone, 2-methyl-1-(4-methylthiophenyl)-2-morpholinopropane-1-one, 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)-butanone-1 and 2,2-dimethoxy-1,2-diphenylethane-1-one are more preferably used.
[0140] The amount of the photopolymerization initiator is preferably 0.01 to 20 parts by mass, more preferably 1 to 10 parts by mass, based on 100 parts by mass of the resin component of the active energy ray-curable coating composition. The photopolymerization initiator may be used alone or in combination of two or more.
[0141] (Other ingredients)
[0142] In the above-mentioned active energy ray-curable coating composition, a compound added as a coating material can usually be contained as other components. As other components, ultraviolet light absorbers (UVA), light stabilizers (HALS), adhesive resins, crosslinking agents, pigments, surface conditioning agents, defoamers, conductive fillers, solvents, etc. can be cited.
[0143] Further, in order to mix the components contained in the active energy ray-curable coating composition or adjust the viscosity, a solvent can be used. As the solvent, for example, as long as one or more of the previously known organic solvents used in esters, ethers, alcohols, amides, ketones, aliphatic hydrocarbons, alicyclic hydrocarbons, aromatic hydrocarbons, etc., are used in combination. It should be noted that when the above-mentioned solvent is used, if volatile substances remain in the laminated film, when the substrate is decorated, the volatile substances volatilize, and sometimes pinholes or expansion are generated. Therefore, it is preferred to fully reduce the volatile substances contained in the laminated film.
[0144] It is further preferred that the active energy ray-curable coating composition further contains 0.5 to 60 parts by weight of an inorganic / organic filler having an average primary particle size of 100 nm or less. Thus, anti-caking properties, high scratch resistance and surface hardness can be improved. The lower limit of the above-mentioned amount is more preferably 1% by weight, and the upper limit is more preferably 50% by weight.
[0145] Examples of the inorganic filler include silica, fine powdered glass, alumina, calcium carbonate, kaolin, clay, sepiolite (magnesium silicate), talc (magnesium silicate), mica (aluminum silicate), xonotlite (calcium silicate), aluminum borate, hydrotalcite, wollastonite (calcium silicate), potassium titanate, titanium oxide, barium sulfate, magnesium sulfate, magnesium hydroxide, yttrium oxide, cerium oxide, silicon carbide, boron carbide, zirconium oxide, aluminum nitride, silicon nitride, or eutectic mixtures thereof, or non-metallic inorganic materials obtained by molding, firing, etc., so-called ceramic fillers. Among them, silica, alumina, zirconium oxide, or eutectic mixtures thereof are preferred in terms of price and effect.
[0146] Examples of the organic filler include beads of resins such as acrylic, styrene, silicone, polyurethane, acrylic urethane, benzoguanamine, and polyethylene.
[0147] In addition, as commercially available products, organic silica sol MIBK-ST, MEK-ST-UP, MEK-ST-L, MEK-AC-2140Z (produced by Nissan Chemical Industries, Ltd.), SIRMIBK15ET%-H24, SIRMIBK15ET%-H83, ALMIBK30WT%-H06 (CIK NanoTek company), etc. can be used.
[0148] The active energy ray-curable coating composition may also contain 0.5 to 20% by weight (solid content ratio in the coating) of a polyisocyanate compound having an isocyanate group. It is preferred from the viewpoint that formability (elongation) and scratch resistance can be imparted by incorporating the polyisocyanate compound. The lower limit of the above-mentioned incorporation amount is more preferably 2% by weight, and the upper limit is more preferably 18% by weight.
[0149] The film thickness of the coating layer is not particularly limited, but is preferably 3 to 60 μm.
[0150] It is preferred to ensure a predetermined film thickness to maintain properties such as surface hardness and scratch resistance. The coating viscosity also depends on the method of forming the coating film, but is preferably 50 mPa·s to 5000 mPa·s, and more preferably 100 mPa·s to 3000 mPa·s. If the viscosity is lower than this value, it is difficult to ensure the film thickness, and the workability is poor. If the viscosity is higher than this value, air will remain, so that problems such as expansion will occur during molding.
[0151] (Design layer)
[0152] The design layer is a coating film of a design layer paint and is a layer that plays a major role in the design of the decorative laminate. As the design layer, a conventionally known base layer of an automotive exterior coating film, a design layer of a decorative laminate, or a colored layer can be used.
[0153] Examples of the resin component of the design layer paint include the resin components exemplified in the above-mentioned clear layer paint.
[0154] In one embodiment, the resin component of the design layer paint includes a thermosetting resin. In another embodiment, the resin component of the design layer paint includes a thermosetting resin and a photocurable resin. In yet another embodiment, the resin component of the design layer paint is only a thermosetting resin.
[0155] The resin components of the design layer coating may be used alone or in combination of two or more.
[0156] The resin component of the design layer coating may be the same as or different from the resin component of the transparent layer coating. From the viewpoint of suppressing the mixing of the design layer and the transparent layer and improving the distinctness of the design of the design layer visually recognized by the observer, it is preferred that the resin component of the design layer coating is different from the resin component of the transparent layer coating, and it is more preferred that the resin component of the design layer is urethane resin.
[0157] The urethane resin contained in the design layer coating is not particularly limited, but the Mw of the urethane resin is preferably 10000 to 200000, and more preferably 30000 to 150000. If the Mw is 10000 or more, the flexibility of the design layer is improved, and if the Mw is 200000 or less, the manufacture of the design layer coating and the coating properties on the substrate film are improved.
[0158] The Tg of the urethane resin is preferably -30 to 30° C. If the Tg of the urethane resin is -30° C. or higher, the viscosity (blocking) of the coating film after application and drying is improved, and if the Tg of the urethane resin is 30° C. or lower, the hardness of the coating film is reduced, the moldability is improved, and the physical properties of the product under low temperature conditions are also improved.
[0159] The amount of the resin component in the design layer paint may be appropriately adjusted, and for example, the amount of the resin component in the design layer paint is 10 to 60% by mass, preferably 20 to 50% by mass, based on the total mass of the design layer paint including the solvent.
[0160] There are no particular limitations on the pigments used in the paint for the design layer, and known pigments can be used. Examples of the pigment include inorganic pigments and organic pigments. Examples of the pigment include metals such as aluminum, copper, zinc, iron, nickel, tin, and aluminum oxide; alloys thereof; bright pigments such as interferometric mica, muscovite, graphite, glass flakes, and aluminum oxide flakes; and flaky bright pigments formed by coating these metals, alloys, interferometric mica, muscovite, graphite, glass flakes, or aluminum oxide flakes with metal oxides (e.g., titanium oxide, titanium dioxide, and iron oxide) or metals (e.g., gold and silver). In addition, for example, there can be mentioned the aluminum oxide flake pigment (a) described in Japanese Patent Publication No. 2016-221473; a flaky bright pigment in which a metal substrate or a glass flake substrate is coated with a metal oxide or a metal; a flaky bright pigment in which a coloring pigment is chemically adsorbed on the surface of a metal substrate or a glass flake substrate; an aluminum pigment having an aluminum oxide layer formed on the surface of an aluminum substrate; an aluminum solid solution plate-like iron oxide pigment; a flaky bright pigment in which the surface of interfering mica, graphite or silica flakes is coated with titanium dioxide; a plate-like iron oxide pigment, etc.
[0161] The amount of the pigment in the design layer paint may be appropriately adjusted, and for example, the amount of the pigment in the design layer paint is 5 to 70% by mass, preferably 3 to 60% by mass, based on the total mass of the design layer paint including the solvent.
[0162] Examples of the solvent for the design layer coating include the solvents exemplified in the above-mentioned clear layer coating, etc. The solvent may be used alone or in combination of two or more.
[0163] The paint for the design layer can be either water-based paint or solvent-based paint.
[0164] The design layer coating may contain, in addition to the resin component and the solvent, conventionally known additives used in design layer coatings. Examples of such additives include the additives exemplified in the clear layer coating.
[0165] The viscosity of the design layer coating material may be appropriately adjusted, and is, for example, 100 to 7000 mPa·s, preferably 300 to 4000 mPa·s.
[0166] In one embodiment, the viscosity of the clear layer coating material is 300 to 2000 mPa·s, and the viscosity of the design layer coating material is 300 to 4000 mPa·s.
[0167] The thickness of the design layer may be appropriately adjusted, and is, for example, 5 to 30 μm, preferably 10 to 25 μm.
[0168] The design layer may be formed of two or more design layers. For example, a first design layer and a second design layer having different materials, thicknesses, etc. of coatings such as resin components and pigments may be combined as the design layer. When there are multiple design layers, the absolute value of the difference between the solubility parameter (SP) value of the resin component of the coating for the transparent layer and the solubility parameter (SP) value of the resin component of the coating for the design layer forming the design layer adjacent to the transparent layer is preferably 0.10 or more.
[0169] (Resin base material)
[0170] As the resin substrate, there is no particular limitation, and known resin substrates and substrate films can be used in the past. As the resin substrate, for example, the films illustrated in the above-mentioned protective film can be cited. For the substrate film, a thermoplastic polyurethane resin film is preferred. Due to the resin substrate, therefore, there is the advantage of being able to peel off without breaking after maintaining the strength of the laminated film and being attached to the adherend. In addition, the construction property when pasting the laminated film is also improved. For example, it is also possible to stretch a soft film while applying force while pasting by manual operation.
[0171] The resin substrate may be a substrate subjected to surface modification treatment such as corona treatment, low-temperature plasma treatment, etc. The substrate film may further contain additives such as a flame retardant, an antistatic agent, and an ultraviolet light inhibitor.
[0172] The thickness of the resin substrate may be appropriately adjusted, and is, for example, 25 to 300 μm, preferably 50 to 200 μm.
[0173] (Adhesive layer)
[0174] The adhesive layer has a function of attaching the laminated film to an object. The adhesive layer is not particularly limited, and conventionally known adhesive layers, bonding layers, double-sided tapes, and adhesives can be used.
[0175] The adhesive layer is used to bond the laminate film to the adherend surface. The adhesive layer provided in the conventional decorative laminate film is for the purpose of permanently bonding the laminate film to the adherend. On the other hand, since the laminate film of the present invention is a peelable laminate film, it is preferred that the adhesive layer has a moderate adhesive force.
[0176] As the adhesive included in the adhesive layer, as long as it is a known adhesive in the past, there is no particular limitation, for example, VYLON UR-3200 (Toyobo Co., Ltd.), UR-1361ET (Toa Synthetics Co., Ltd.), SK Dyne (registered trademark) (Soken Chemical Co., Ltd.) etc. can be cited. The above-mentioned adhesive can be formed by applying the above-mentioned adhesive and drying, and can also be formed by laminating adhesive sheets. The adhesive layer can use various known materials, as resin, preferably acrylic resin, urethane resin, polyester resin, silicone resin and rubber resin etc., preferably with isocyanate cross-linked resin. In addition, preferably comprising a coupling agent, also preferably with glass bonding film lamination etc. Specifically, as the resin, acrylic resin Alotane 2050-55 manufactured by Nippon Shokubai Co., Ltd. is preferably used, as the coupling agent, KBM-803, KBM-903, KBM-9007N, KBE-9013, X12-1056ES manufactured by Shin-Etsu Chemical Co., Ltd. is preferably used, and the film can be preferably OCA film 8211, 8212, 8213, 8146-1 manufactured by 3M Company.
[0177] From the viewpoint of ensuring the close adhesion between the adhesive layer and the object and exhibiting a peeling force that can be peeled off as required, the adhesive layer preferably contains an acrylic resin and an isocyanate compound. In addition, additives such as a flame retardant, an antistatic agent, and an ultraviolet inhibitor may also be contained.
[0178] From the viewpoint of ensuring the close adhesion between the pressure-sensitive adhesive layer and the object and exhibiting a peeling force sufficient to enable peeling as required, the peeling force of the pressure-sensitive adhesive layer with respect to the object is preferably 1.0 to 50.0 N / 25 mm.
[0179] The appropriate adhesive strength of the adhesive layer can be expressed, for example, as an adhesive strength in the range of 1.0 N / 25 mm to 50.0 N / 25 mm when the laminated film is peeled from the resin substrate.
[0180] If the adhesive force is more than 50.0N / 25mm, it has the same adhesive force as the general adhesive layer, so it is completely attached to the adherend and difficult to peel off again. On the other hand, if the adhesive force is less than 1.0N / 25mm, the adhesive force is insufficient and it is easy to float. By the adhesive force being within the range as described above, it can be easily peeled off. The above-mentioned adhesive force can be measured by known methods such as peel strength tester (ADY Co., Ltd. system).
[0181] The thickness of the adhesive layer may be appropriately adjusted, and is, for example, 5 μm to 2 mm, preferably 10 to 50 μm.
[0182] In one embodiment, the adhesive layer has a release film on the surface opposite to the resin substrate, and the surface roughness of the release film on the adhesive layer side is 20 to 100 nm.
[0183] (Adherent)
[0184] The purpose of the adherend is to adhere the laminated film L, and the material, hardness, etc. are not particularly limited, and a conventionally known resin plate or the like can be used.
[0185] In one embodiment, the arithmetic mean roughness of the adherend surface is 0.01 to 0.6 μm.
[0186] (Laminated film L)
[0187] The laminated film L refers to a laminated film having no protective film by peeling the protective film from the laminated film at a rate of 5.0 mm / sec.
[0188] The surface roughness Rac of the coating surface of the laminate film L opposite to the resin substrate (i.e., the surface after peeling off the protective film) and the surface roughness Rap of the coating surface of the protective film after peeling off (i.e., the surface in contact with the coating) satisfy the following formula 1.
[0189] 50.0≤(Rac / Rap)×100≤210.0 Formula 1
[0190] By transferring the surface shape of the protective film to the coating layer, the surface shape of the laminate film L can be changed, thereby changing (designing) the optical properties (gloss). In addition, no change in the optical properties was observed under high temperature and high humidity conditions.
[0191] When the Rap of the protective film is 0.1 μm or more, the value of the above formula is preferably 60 or more and 135 or less.
[0192] If the ratio is less than 50, the film becomes too hard, so the protective film is peeled off and any optical properties corresponding to the requirements cannot be provided.
[0193] If the molecular weight is greater than 210, the film becomes too soft, so that the protective film is difficult to peel off and any optical properties as required cannot be provided.
[0194] The surface free energy γac of the coating layer of the laminate film L on the opposite side to the resin substrate and the surface free energy γap of the coating layer side of the protective film peeled off from the laminate film at a speed of 5.0 mm / sec satisfy the following formula 2.
[0195] 50.0≤(γac / γap)×100≤110.0 Formula 2
[0196] In the same manner as described above, the surface shape of the protective film can be transferred to the coating layer.
[0197] If the molecular weight is less than 50, the film becomes too hard, so that the protective film is difficult to peel off and any optical properties as required cannot be provided.
[0198] If the molecular weight is greater than 110, the film becomes too soft, so the protective film is peeled off and any optical properties as required cannot be provided.
[0199] The 60° glossiness G(IL) of the laminated film L and the 60° glossiness G(IC) of the laminated film L in the composite of the laminated film L and the adherend when the laminated film L is bonded to the adherend satisfy the following formula 3.
[0200] 85.0≤(G(IC) / G(IL))×100≤110.0 Formula 3
[0201] Preferably, 95.0≤(G(IC) / G(IL))×100≤105.0.
[0202] If it is less than 85.0, unreacted portions remain and the film becomes soft. Therefore, when an object having surface irregularities is bonded to an adherend using a roller or the like, the surface becomes rough or is affected by the surface roughness of the adherend.
[0203] Alternatively, the film becomes too hard and cracks may occur when the film is bonded to an adherend, and any optical properties may not be maintained.
[0204] If it is greater than 120.0, unreacted portions remain and the film becomes soft. Therefore, when an object without surface irregularities is bonded to an adherend using a roller or the like, the surface becomes rough or is affected by the surface roughness of the adherend.
[0205] The Martens hardness of the coating layer of the laminate film L satisfies the following Formula 5.
[0206] 2N / mm 2 ≤HM(L)≤50N / mm 2 Formula 5
[0207] If less than 2N / mm 2 , the film becomes too soft and its shape changes after the wet heat test, and a laminated film with excellent durability cannot be provided.
[0208] If greater than 50N / mm 2 , the film becomes too hard and cracks occur after the wet heat test, and a laminated film with excellent durability cannot be provided.
[0209] The 60° gloss G(A) of the surface of the laminated film L after the composite is treated under the conditions of humidity 85% and temperature 85°C for 1500 hours and the 60° gloss G(IC) of the surface of the laminated film L before the wet heat test of the composite under the conditions of humidity 85% and temperature 85°C satisfy the following formula 5.
[0210] 70.0≤(G(A) / G(IC))×100≤120.0 Formula 5
[0211] Preferably, 80.0≤(G(A) / G(IC))×100≤110.0.
[0212] If it is less than 70.0, unreacted sites remain and the film becomes soft. Therefore, there is no surface irregularity before the wet heat resistance test, and a flat laminated film cannot maintain its surface shape after the wet heat test and has a rough surface, thereby failing to provide a laminated film with excellent durability.
[0213] If it is greater than 120.0, unreacted sites remain and the film becomes soft. Therefore, a laminated film having surface irregularities before the moisture and heat resistance test cannot maintain its surface shape after the moisture and heat resistance test and has a rough surface, thereby failing to provide a laminated film having excellent durability.
[0214] The Tg of the coating layer of the laminate film L after curing is 25.0°C to 120.0°C.
[0215] If the Tg is less than 25.0°C, the coating is tacky at room temperature and cannot provide any optical properties after the protective film is peeled off.
[0216] If Tg is higher than 120.0°C, the coating becomes too hard and cracks may occur after a wet heat test, thereby failing to provide a laminated film having excellent durability.
[0217] The stretching ratio of the laminated film L is 50% to 300%, and more preferably 100% to 200%.
[0218] If the value is less than 50.0, the film becomes too hard and cracks are easily generated when bonded to an adherend, and any optical properties cannot be maintained.
[0219] If greater than 300.0, the film becomes too soft, and when attached to an adherend, it is easily affected by the bottom layer and cannot maintain any optical properties. In addition, the film becomes too soft, and therefore, when peeling off the protective film, it cannot maintain the shape and cannot provide any optical properties corresponding to the needs.
[0220] (thing)
[0221] The article of the present invention includes an adherend and a laminate film L obtained by peeling off the protective film from the laminate film, and the adhesive layer of the laminate film L is in contact with the adherend.
[0222] Example
[0223] The present invention will be described in further detail below with reference to examples. These examples are intended to illustrate the present invention and do not limit the present invention in any way.
[0224] The protective films used in Examples are as follows.
[0225] Glossiness protection film: trade name "Iupilon A4160" manufactured by Toyobo Co., Ltd., PET film, thickness 50 μm.
[0226] Matte protective film: trade name "KB film" manufactured by Kimoto Co., Ltd., PET film, thickness 188 μm.
[0227] The details of the components of the thermosetting coating material for a coating (clear) layer used in the examples are as follows.
[0228] Acrylic resin: trade name "LR2731" manufactured by Mitsubishi Rayon Inc., Tg: 20°C, Mw: 5500, hydroxyl value: 170 mgKOH / g, solid content: 70%.
[0229] Fluororesin: "Lumiflon LF600X", trade name, manufactured by AGC Corporation, hydroxyl value of 50 mgKOH / g, solid content of 50%.
[0230] Silicone resin: trade name "BYK-SILCLEAN 3700" manufactured by BYK, hydroxyl value of 30 mgKOH / g, solid content of 25%.
[0231] Polycarbonate polyol: trade name "Duranol T5650E" manufactured by Asahi Kasei Corporation, hydroxyl value: 225 mgKOH / g.
[0232] Polycaprolactone polyol: trade name "PLACCEL 210" manufactured by Daicel Corporation, Tg is 20°C or less, Mw is 1000, and hydroxyl value is 110 mgKOH / g.
[0233] UVA1: Benzotriazole compounds.
[0234] UVA2: Triazine compounds.
[0235] HALS: hindered amine compounds.
[0236] Additive 1: Heat-reactive silicone compound.
[0237] Additive 2: Thermally reactive fluorine compound.
[0238] Curing agent: trade name "H-2550" manufactured by NIPPON PAINT AUTOMOTIVE COATINGS CO., LTD., isocyanate compound.
[0239] The details of the components of the active energy ray-curable coating (clear) layer coating material used in the examples are as follows.
[0240] Multifunctional acrylate: trade name "Aronix M-315" manufactured by Toagosei Co., Ltd.
[0241] Urethane acrylate: trade name “CN-9893” manufactured by Arkema.
[0242] Photopolymerization initiator: α-hydroxyacetophenone.
[0243] The details of the components of the design layer coating material used in the examples are as follows.
[0244] Polyacrylic acid polyol: trade name “COATAX A-200” manufactured by Toray Fine Chemicals Co., Ltd.
[0245] Pigment: "Xirallic (registered trademark) T60-23 SW Galaxy Blue", trade name, manufactured by Merck.
[0246] Curing agent: trade name "H-2550" manufactured by NIPPON PAINT AUTOMOTIVE COATINGS CO., LTD., isocyanate compound.
[0247] The details of the resin substrate used in the examples are as follows.
[0248] Resin substrate: a thermoplastic polyurethane resin film manufactured by Nihon Matai Co., Ltd. under the trade name “Esmer PX98”, with a thickness of 150 μm.
[0249] The details of the adhesive layer composition used in the examples are as follows.
[0250] Acrylic resin: trade name "SK Dyne 1811L" manufactured by Soken Chemical Co., Ltd., Tg: -7°C, Mw: 5500, solid content: 70%.
[0251] Isocyanate compound: trade name "TD-75" manufactured by Soken Chemical Co., Ltd.
[0252] (Preparation of a heat-curable coating material for a (clear) layer)
[0253] Acrylic resin, polycarbonate polyol and polycaprolactone polyol were mixed in the proportions (parts by mass) shown in Table 1. After mixing, UVA, HALS, additives and a curing agent were mixed, and the mixture was diluted with methyl ethyl ketone to adjust the viscosity as needed to prepare a thermosetting coating material.
[0254] (Preparation of active energy ray-curable coating material)
[0255] Polyfunctional urethane acrylate and polyurethane acrylate were mixed in the proportion (parts by mass) shown in Table 2. After the mixing, a photopolymerization initiator was added to prepare an active energy ray-curable coating material.
[0256] (Preparation of coating for design layer)
[0257] The pigment was mixed with the polyacrylic polyol in the proportion (parts by mass) shown in Table 2. After the mixing, a curing agent was added, and the mixture was further diluted with methyl ethyl ketone to adjust the viscosity as needed to prepare a coating material for a design layer.
[0258] (Example 1)
[0259] A thermosetting coating paint was applied to one surface of the resin substrate using a Baker-type coater so that the dry film thickness was 25 to 30 μm, and then the uncured coating was heated at a temperature of 120° C. for 2.5 minutes to form a coating. Then, a matte protective film was laminated on the surface of the coating at a temperature of 23° C. using a laminator or the like. After lamination, the coating was cured by aging at 50° C. for 4 days.
[0260] The adhesive layer composition was applied to the surface of the resin substrate opposite to the surface on which the coating layer was formed using a Baker-type coater so that the dry film thickness was 30 μm, and dried at 100° C. for 5 minutes to form an adhesive layer. Then, the spacer and the adhesive layer were bonded together using a laminator or the like, and aged at 50° C. for 7 days to obtain a laminated film having an adhesive layer.
[0261] (Examples 2 to 6)
[0262] A laminated film was produced by the same procedure as in Example 1 except that the type of protective film, heating temperature, resin ratio, and curing amount were changed as shown in Table 1.
[0263] (Example 9)
[0264] The active energy ray-curable coating material was applied to one surface of the resin substrate using a rod coater so that the dry film thickness was 10 μm. Then, the uncured coating was heated at 80°C for 1.0 minute to form a coating. Then, a matte protective film was laminated on the surface of the coating using a laminator or the like at a temperature of 23°C. After lamination, the irradiation was performed with a cumulative light dose of 2000 mJ / cm 2 Active energy rays are used to cure the coating.
[0265] The adhesive layer composition was applied to the surface of the resin substrate opposite to the surface on which the coating layer was formed using a Baker-type coater so that the dry film thickness was 30 μm, and dried at 100° C. for 5 minutes to form an adhesive layer. Then, the spacer and the adhesive layer were bonded together using a laminator or the like, and aged at 50° C. for 7 days to obtain a laminated film having an adhesive layer.
[0266] (Example 10)
[0267] Except that the type of the protective film was changed as described in Table 2, the same procedure as in Example 9 was carried out to produce a laminated film.
[0268] (Example 11)
[0269] The design layer coating is applied to one surface of the resin substrate with a Baker-type coater in a dry film thickness of 20 μm, and then the uncured design layer is heated at a temperature of 100°C for 5 minutes to form a design layer. Then, a protective film is laminated on the surface of the design layer at a temperature of 23°C using a laminator or the like. After lamination, the design layer is cured by aging at 50°C for 7 days. A thermosetting transparent layer coating is applied to the cured design layer with a Baker-type coater in a dry film thickness of 25 to 30 μm, and then the uncured thermosetting coating is heated at a temperature of 120°C for 2.5 minutes to form a thermosetting transparent layer. Then, a matte protective film is laminated on the surface of the thermosetting transparent layer using a laminator or the like at a temperature of 23°C. After lamination, the thermosetting transparent layer is cured by aging at 50°C for 4 days.
[0270] The adhesive layer composition was applied to the surface of the resin substrate opposite to the surface on which the design layer and the coating layer were formed using a Baker-type coater so that the dry film thickness was 30 μm, and dried at 100° C. for 5 minutes to form an adhesive layer. Then, the spacer and the adhesive layer were bonded together using a laminator or the like, and aged at 50° C. for 7 days to obtain a laminated film having an adhesive layer.
[0271] (Examples 12 to 14)
[0272] A laminated film was produced by the same procedure as in Example 11 except that the resin ratio and the protective film were changed as described in Table 3.
[0273] (Example 15)
[0274] The design layer coating is applied to one surface of the resin substrate with a Baker-type coater in a dry film thickness of 20 μm, and then the uncured design layer is heated at a temperature of 100°C for 5 minutes to form a design layer. Then, a protective film is laminated on the surface of the design layer at a temperature of 23°C using a laminator or the like. After lamination, the design layer is cured by aging at 50°C for 7 days. A thermosetting coating is applied to the surface of the resin substrate opposite to the surface coated with the design layer with a Baker-type coater in a dry film thickness of 25 to 30 μm, and then the uncured coating is heated at a temperature of 120°C for 2.5 minutes to form a coating. Then, a matte protective film is laminated on the surface of the coating at a temperature of 23°C using a laminator or the like. After lamination, the coating is cured by aging at 50°C for 4 days. The adhesive layer composition was applied to the surface of the resin substrate on which the design layer was formed using a Baker-type coater so that the dry film thickness was 30 μm, and dried at 100° C. for 5 minutes to form an adhesive layer. Then, the spacer and the adhesive layer were bonded together using a laminator or the like, and aged at 50° C. for 7 days to obtain a laminated film having an adhesive layer.
[0275] (Example 15)
[0276] A laminated film was produced by the same procedure as in Example 15 except that the protective film was changed as described in Table 4.
[0277] (Comparative Examples 1 to 7)
[0278] A laminated film was produced by the same procedure as in Example 1 except that the type of protective film, heating temperature, and curing amount were changed as described in Table 5.
[0279] Table 1
[0280]
[0281] Table 2
[0282]
[0283] Table 3
[0284]
[0285] Table 4
[0286]
[0287] Table 5
[0288]
[0289] - Partial: Indicates items that could not be measured due to failure to transfer.
[0290] Determination method of arithmetic mean roughness (Ra)
[0291] The test sample was cut into 50 mm×50 mm, and each arithmetic mean roughness (Ra) value was measured in accordance with JIS B0601; 2001 using a laser microscope (VK8700, manufactured by KEYENCE) equipped with an eyepiece lens having a magnification of 20 times and an objective lens having a magnification of 50 times.
[0292] The arithmetic mean roughness (Rac) of the protective film side of the coating layer of the laminate film L after peeling the protective film at a speed of 5.0 mm / sec and the arithmetic mean roughness (Rap) of the surface of the laminate film L side of the protective film were measured, and the value of (Rac / Rap)×100 was calculated.
[0293] Calculation method of surface free energy
[0294] The test sample was cut into 50 mm × 50 mm pieces, and the contact angles of DIW (ion exchange water) and diiodomethane were measured using an automatic contact angle meter (Dmo-701, manufactured by Kyowa Interface Science Co., Ltd.) at an environment of 20°C to 23°C, with a droplet size of 1 μL and 1 second after the droplet was dropped, for the protective film side of the laminated film after the protective film was peeled off at a speed of 5.0 mm / sec and the surface of the laminated film side after the protective film was peeled off. The surface free energies of each surface were calculated according to the Owens-Wendt formula.
[0295] The surface free energy γac of the protective film side of the laminated film after peeling off the protective film at a speed of 5.0 mm / sec was obtained. The surface free energy γap of the protective film side of the laminated film after peeling off the protective film at a speed of 5.0 mm / sec was also obtained using the same procedure. γac / γap×100 was calculated based on the obtained values of each surface free energy.
[0296] Martens hardness test method
[0297] After the test sample was cut into 50mm×50mm and attached to a glass plate, the Martens hardness HM (L) of the laminated film was measured according to the indentation depth under the maximum load conditions using a HM2000 micro hardness tester manufactured by Fischer, with a Vickers diamond indenter, a load speed of 5mmN / 20s, and a creep of 5s.
[0298] Determination method of 60° gloss
[0299] The test sample was cut into 100 mm × 50 mm, and a black PET film (manufactured by PANAK Co., Ltd., trade name: Gel Poly GPH100E82A04) was attached to the surface of the adhesive layer of the laminated film opposite to the resin substrate, and the 60° gloss (G(IL)) was measured using a gloss meter (micro-Tri-gloss BYK).
[0300] Regarding the 60° glossiness (G(IC)) of the surface of the laminated film L of the composite when attached to the adherend, the surface of the adhesive layer of the laminated film opposite to the resin substrate was attached to a 1 mm polycarbonate plate to obtain a composite. A black PET film was attached to the surface of the polycarbonate plate of the composite opposite to the surface attached to the laminated film, and the 60° glossiness (G(IC)) of the composite was measured using a gloss meter. In addition, the composite was placed in a constant temperature and humidity chamber manufactured by ESPEC in a manner not to contact the wall surface, and the 60° glossiness G(A) of the surface of the laminated film L after treatment for 1500 hours was similarly measured under the conditions of a humidity of 85% and a temperature of 85°C.
[0301] From the obtained glossiness value at 60°, the values of G(IC) / G(IL)×100 and G(A) / G(IC)×100 were calculated.
[0302] Determination of glass transition temperature
[0303] The cured film on the surface of the protective film side of the laminated film after peeling off the protective film at a speed of 5.0 mm / second was scraped with a knife as a test sample. The glass transition temperature is measured by the following process using a differential scanning calorimeter (DSC) (thermal analysis device SSC5200 (Seiko Instruments Inc.)). Specifically, in the process of heating from -40°C to 200°C at a heating rate of 5°C / min (process 1), the process of cooling from 200°C to -40°C at a cooling rate of 5°C / min (process 2), and the process of heating from -40°C to 200°C at a heating rate of 5°C / min (process 3), the value obtained according to the graph during heating in process 3 is used as the glass transition temperature.
[0304] Determination method of elongation
[0305] The laminated film L was cut into 10 mm × 70 mm, and 10 mm of each end portion was fixed by the clamping part of a precision universal testing machine (universal testing machine (manufactured by Shimadzu Corporation)). After fixing, the film was stretched at a speed of 200 mm / min under an environment of 23°C, and the length L (A) of the film until cracks (ruptures) appeared in the coating was measured.
[0306] The length of the film before the test was defined as L(B), and the elongation was calculated according to the following formula: L(A) and L(B) do not include the length of the portion fixed by clamping.
[0307] Elongation (%) = (L(A) - L(B)) / L(B) × 100
[0308] Evaluation method of transferability
[0309] The protective film was peeled off from the laminated film, and the appearance of the laminated film surface was visually confirmed. Whether the unevenness of the protective film was transferred to the coating layer was evaluated in the following two stages.
[0310] Good: The transfer property is good.
[0311] Bad: Transfer is poor.
[0312] Optical properties evaluation method
[0313] When the adherend was bonded to the laminate film L, whether or not any optical characteristics were obtained was evaluated in the following four stages based on the change rate between the glossiness G(IL) of the adherend before bonding and the glossiness G(IC) of the laminate film bonded to the adherend.
[0314] |G(IC)―G(IL)| / G(IC)×100(%)
[0315] A: The change rate is less than 5%.
[0316] B: The change rate is 5% or more and less than 10%.
[0317] C: The change rate is 10% or more and less than 20%.
[0318] D: The change rate is 20% or more.
[0319] Evaluation method for moisture and heat resistance
[0320] The laminate film L was cut into a size of 100 mm×50 mm and bonded to an adherend, and exposed to the conditions of temperature 85°C and humidity 85% for 1500 hours. The change rate of 60° glossiness before and after the wet heat test was evaluated in the following four stages.
[0321] The change rate was calculated by the following formula.
[0322] |G(A)―G(IC)| / G(IC)×100(%)
[0323] A: The change rate is less than 5%.
[0324] B: The change rate is 5% or more and less than 10%.
[0325] C: The change rate is 10% or more and less than 50%.
[0326] D: The change rate is 50% or more, or appearance defects such as cracks occur.
[0327] Industrial Applicability
[0328] According to the present invention, an object is to provide a laminated film which provides optical properties corresponding to requirements without being affected by the gloss and surface roughness of an adherend and has excellent durability even under conditions of severe moisture resistance of the adherend.
[0329] Description of Reference Numerals
[0330] 1: Laminated film.
[0331] 2: Laminated film L.
[0332] 3: Complex.
[0333] 4: Laminated film
[0334] 5: Laminated film.
[0335] 10: Protective film.
[0336] 20: Coating.
[0337] 30: Resin substrate. 40: Adhesive layer.
[0338] 50: adherend.
[0339] 60: Transparent layer.
[0340] 70: Design layer.
Claims
1. A laminated film comprising a protective film, a coating layer, a resin substrate, and an adhesive layer in this order, wherein: The protective film is adjacent to the coating layer, and when the protective film is peeled off from the laminated film at a speed of 5.0 mm / sec and the laminated film without the protective film is set as the laminated film L, the surface roughness Rac of the surface of the coating layer of the laminated film L on the side opposite to the resin substrate and the surface roughness Rap of the coating layer side of the protective film after peeling satisfy Formula 1, 50.0≤(Rac / Rap)×100≤210.0 Formula 1 Furthermore, the surface free energy γac of the surface of the coating layer of the laminate film L on the side opposite to the resin substrate and the surface free energy γap of the coating layer side of the protective film after peeling satisfy Formula 2, 50.0≤(γac / γap)×100≤110.0 Formula 2 The 60° glossiness G(IL) of the laminated film L and the 60° glossiness G(IC) of the laminated film L in the composite of the laminated film L and the adherend when the laminated film L is bonded to the adherend satisfy Formula 3, 85.0≤(G(IC) / G(IL))×100≤110.0 Formula 3 Furthermore, the Martens hardness of the coating layer of the laminated film L satisfies Formula 4, 2 N / mm 2 ≤ HM(L) ≤ 50 N / mm 2 Equation 4 The 60° gloss G(A) of the laminated film L after the wet heat test of the composite under the conditions of 85% humidity and 85°C and the 60° gloss G(IC) of the laminated film L before the wet heat test of the composite under the conditions of 85% humidity and 85°C satisfy Formula 5, 70.0≤(G(A) / G(IC))×100≤120.0 Equation 5.
2. The laminated film according to claim 1, wherein The coating layer is formed of at least one layer, and the laminated film is laminated with a protective film, a transparent layer, a design layer, a resin substrate, and an adhesive layer in this order.
3. The laminated film according to claim 1 or 2, wherein: The laminated film is formed of a structure including a design layer between a resin base material and an adhesive layer of the laminated film, and the laminated film is formed by laminating a protective film, a coating layer, a resin base material, a design layer, and an adhesive layer in this order.
4. The laminated film according to any one of claims 1 to 3, wherein The Tg of the coating layer of the laminate film L after curing is 25.0°C to 120.0°C.
5. The laminated film according to any one of claims 1 to 4, wherein The stretching ratio of the laminated film L is 50% to 300%.
6. The laminated film according to any one of claims 1 to 5, wherein The coating layer is composed of one or more selected from the group consisting of acrylic resin, polycarbonate polyol, fluororesin, and silicone resin.
7. An article, wherein The article comprises an adherend and a laminated film L, wherein the laminated film L is a laminated film L obtained by peeling the protective film from the laminated film according to any one of claims 1 to 6. The adhesive layer of the laminate film L is in contact with the adherend.
Citation Information
Patent Citations
JP1979026159B2
Multilayer coating film forming method
JP2016221473A
Laminated film
JP2018053193A
Laminate, surface-protected article, method for manufacturing laminate
WO2016010041A1
Film for plastic restoration, surface-protected article, and process for producing film for plastic restoration
WO2017047600A1